Novel nano-Y2O3/myristic myristic acid nanocomposite PCM for cooling performances of electronic device with various fin designs - Gur, Muhammed; Gurgenc, Ezgi; Cosanay, Hakan; Öztop, Hakan Fehmi (Elsevier, 2024)
Effective thermal management is critical for enhancing the longevity and operational efficiency of electronic devices. This research introduces a novel cooling approach by incorporating Yttrium Oxide (Y2O3) nanoparticles into Phase Change Materials (PCMs) to improve thermal management in electronic devices. This study focuses on developing nanocomposite PCMs with Y2O3 nanoparticles embedded in a myristic acid (MA) matrix through melting and physical mixing. Nanoparticles were added to MA at various mass fractions: 0.5 %, 1 %, 1.5 %, and 2 %. Structural and morphological analyses were conducted using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), and field emission scanning electron microscopy combined with energy dispersive X-ray spectroscopy (FE-SEM-EDX). Thermophysical properties were characterized using differential scanning calorimetry (DSC) and thermal conductivity measurements with the KD2-Pro device. The inclusion of Y2O3 nanoparticles significantly enhanced the thermal conductivity of the PCM, reaching up to 0.229 W/mK in the solid phase and 0.177 W/mK in the liquid phase, representing improvements of 43.125 % and 18 %, respectively, over the base PCM. The highest average specific heat capacity (Cp) values in the solid and liquid phases were 1.98 J/gdegrees C and 2.69 J/gdegrees C, respectively, for the 2 % nanoparticle-additive sample. DSC analysis indicated slight shifts in phase transition temperatures and a noticeable reduction in latent heat values, from 215 J/g to 202 J/g for solidification and from 209 J/g to 201 J/g for melting. Computational analysis using ANSYS-FLUENT software validated the enhanced thermal dissipation properties of the nanocomposite PCM. Additionally, an examination of fin configurations within the PCM containers revealed that rectangular fins provided superior cooling efficacy compared to trapezoidal ones. This study demonstrates that the development of nano- Y2O3 enhanced MA nanocomposite PCMs presents a promising avenue for applications in electronic device thermal management and thermal energy storage.
Keywords: Electronic cooling efficiency; Rare earth enhanced PCM; Computational fluid dynamics; Advanced thermal management; Energy efficient cooling solutions